The Effects of Redundancy in Bimodal Word Processing - Lewandowski, Lawrence J.; Kobus, David A. (Human performance, 1993)
Numerous studies have demonstrated a redundant signals effect (people respond faster to simultaneously presented redundant signals than to single signals) for reaction time on bimodal divided attention tasks when subjects respond to simple stimuli (i.e., lights and tones, letters, and targets). In this study, the effect of stimulus redundancy was examined for complex stimuli (words) on a higher cognitive process (word recall). The results from two separate samples were consistent in showing no advantage of stimulus redundancy in a lexical decision task on RT or decision accuracy, but results did show a significant gain in word recall when the same category word was presented concurrently in the auditory and visual channels. These results suggest that the benefits of bimodal redundancy are not limited to simple stimuli and speed of processing, but they are likely to extend to more complex stimuli and cognitive processes.